Temporal dynamics of microbial community in soil during phytoremediation field experiment - Jaanis Juhanson (Journal of Environmental Engineering and Landscape Management, 2007)
Oil‐shale chemical industry creates approximately 600 000 tons of thermally processed oil shale solid wastes (semi‐coke) every year in Estonia. A field phytoremediation and bioaugmentation experiment has been monitored for three years in the solid waste depository area of oil‐shale chemical industry. We found enhanced degradation rates of pollutants in plots with vegetation and added bacterial biomass. The concentration of volatile phenols had decreased almost by 100 %, and the concentration of oil products had decreased approximately 3 times in planted plots compared to the control plots. The degradation rates were the highest in the upper soil layer which has the highest root density. Vegetation also changed the microbial community structure in comparison with the control plots. In addition to the vegetation, properties of the substrate had an essential effect on the microbial community.